2018
DOI: 10.1111/hex.12675
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing a brief clinic‐based lung cancer screening decision aid for primary care settings

Abstract: BackgroundCancer screening‐related decisions require patients to evaluate complex medical information in short time frames, often with primary care providers (PCPs) they do not know. PCPs play an essential role in facilitating comprehensive shared decision making (SDM).ObjectiveTo develop and test a decision aid (DA) and SDM strategy for PCPs and high‐risk patients.DesignThe DA was tested with 20 dyads. Each dyad consisted of one PCP and one patient eligible for screening. A prospective, one‐group, mixed‐metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…A study that included rural providers in New Mexico suggested that the development of decision-making tools, in conjunction with continuing medical education, would be the most effective way to ensure that providers are able to effectively educate their patients about LDCT screening. Decision aids have been tested in urban populations and have been found to be a helpful and effective tool to educate patients about LDCT screening [32,38,39]. However, when analyzed outside the intervention (eg, randomized trial) context, the quality and length of such screening discussions between patients and their providers is suboptimal, with virtually no mention of potential LDCT screening harms [40].…”
Section: Provider-patient Communicationmentioning
confidence: 99%
“…A study that included rural providers in New Mexico suggested that the development of decision-making tools, in conjunction with continuing medical education, would be the most effective way to ensure that providers are able to effectively educate their patients about LDCT screening. Decision aids have been tested in urban populations and have been found to be a helpful and effective tool to educate patients about LDCT screening [32,38,39]. However, when analyzed outside the intervention (eg, randomized trial) context, the quality and length of such screening discussions between patients and their providers is suboptimal, with virtually no mention of potential LDCT screening harms [40].…”
Section: Provider-patient Communicationmentioning
confidence: 99%
“…Figure 1 depicts the SHARED Project’s three key areas of innovation: (a) intentionally targeting black men as the population with the highest risk of lung cancer disparities, (b) engaging black male citizen scientists as an emerging community engagement model, and (c) integrating multiple theoretical frameworks. Citizen scientists will use the Integrated Model of Stages in the Cultural Adaption of Evidence-Based Intervention to adapt the Agency for Healthcare Research and Quality LDCT decision aid to the informational, language, and cultural needs of black men at an elevated risk of lung cancer (Carter-Harris & Gould, 2017; McDonnell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, joint discussions between patients and health care providers have been mandated by Medicare in the lung screening process to support informed decision making . Supporting informed and equitable lung screening uptake is an anticipated challenge in the UK . Decisions about screening uptake require weighing up complicated information and a high degree of “health literacy”, the comprehension of health information in order to make a well‐founded choice.…”
Section: Discussionmentioning
confidence: 99%
“…Poor levels of health literacy found have also been found in older UK smokers, the key target group for lung screening. In the United States, some decision aids have been developed and tested with promising results for supporting decision making; however, the readability of online aids has been challenged and further testing is needed . In the UK, there are currently no guidelines for developing quality assured lung screening patient literature or established decision‐making tools.…”
Section: Discussionmentioning
confidence: 99%